KINERJA UNDAGI DALAM PEMBANGUNAN PERUMAHAN - Alit, I Ketut (Jurnal Natah, 2003)
nment development. Their education pattern is approaching from non-formal education that is hereditarily assigned from generation to generation. Their knowledge covers both material and spiritual conception that is obtained by learning process, working and praying to compose the output as dharma. All is indeed proposed to harmonious life in a cosmos to attain the prosperity both material and spiritual.The performance of undagi always ensue the process as in the rules, custom, social, ritual and letter that are written on many manuscripts of such palm leaves. Their product is a special and unique that is now facing a hidden crisis from many problems such as how undagi should perform to confront the architecture development in particular the housing development that is becoming complex in global era.At the present, the role of undagi is challenged on a formal education that has a syllabus by clearly direct and education purpose in implementing of teaching-learning process. Nevertheless, undagi is an architect but architect is of course, not undagi. Thus, undagi still has a role in society although their working scope become weighed down because the rapid development of knowledge, technology and art.